Uso de saponina de quilaia (Quillaja saponaria Molina) em juvenis de pacu - Fernandes, Rosangela do Nascimento [UNESP] (2014)
The quillaja saponin (QS) is present in the bark of Chilean and Brazilian trees of the same family, Rosaceae and, it´s able to promote performance and the immune system of animals. Thus, this study evaluated the effect of consuming diets containing increasing levels of QS (0,0; 100,0; 200,0; 300,0; 400,0 mg kg-1) by pacu. Three distinct steps in different consumption diets periods compound by seven, 15, and 30 days. At each step, was used a total of 350 fish, totaling 1050 fishes. These fishes were distributed into 25 cages (200L), in a completely randomized design. In the second chapter, after the feeding period (seven, 15 and 30 days), fish were anesthetized to blood collect and organs for physiological, histological and performance evaluation. The parameters evaluated were the performance (weight gain, apparent feed conversion and feed intake), survival, physiological and histological parameters [hepatosomatic index (HSI), blood cortisol, glucose, cholesterol, triglycerides and intestine histology]. The addition of all levels of QS in the diets of juvenile pacu reduced the triglycerides levels at seven days and HSI at 30 days of feeding. At 15 days of feeding QS diets were observed signals intestinal inflammation in pacu. There was no mortality during the experimental period. In the third chapter, after the feeding period (seven, 15 and 30 days), about 325 fishes were inoculated with the Aeromonas hydrophila and transferred to another experimental system, divided into 25 cages (160L) and during six days were observed clinical signs of disease and occurrence of mortality. The fishes were anesthetized for blood collection before and after bacterial challenge. The physiological analyzes were glucose, total protein and albumin. The immunological variables measured were activity serum lysozyme, leukocytes respiratory activity (LRA), differential and leukocyte count and globulin and ...